2022
DOI: 10.1016/j.idnow.2022.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospital admission and adverse outcome for COVID-19: Role of social factors and medical care

Abstract: Background: Beyond sex, age, and various comorbidities, geographical origin and socio-economic deprivation are associated with Coronavirus Disease (COVID-19) morbidity and mortality in the general population. We aimed to assess factors associated with severe forms of COVID-19 after a hospital emergency department visit, focusing on socio-economic factors. Methods: Patients with laboratory-confirmed COVID-19 attending the emergency department of Béclère Hospital (France) in March-April 2020 were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is known that additional diseases increase disease severity and hospitalization in COVID-19 patients. In Beaumont et al’s study conducted on 399 COVID-19 patients, obese or diabetic individuals were found to have a higher risk of hospitalization than those who did not [ 30 ]. Studies have shown that the most common comorbidities of COVID-19 are DM, HT, and ischemic heart disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that additional diseases increase disease severity and hospitalization in COVID-19 patients. In Beaumont et al’s study conducted on 399 COVID-19 patients, obese or diabetic individuals were found to have a higher risk of hospitalization than those who did not [ 30 ]. Studies have shown that the most common comorbidities of COVID-19 are DM, HT, and ischemic heart disease [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this association remains controversial. Some studies have indicated that patients with greater deprivation scores are at a higher risk of hospitalization and ICU admission ( 12 , 13 ), while other studies have found no association between social deprivation and hospitalization ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%